Linking Religiosity and Employee Performance in the Public Sector: Does Public Service Motivation Matter? - Wayu Eko Yudiatmaja; Edison Edison; Rahayu Sulistiowati; Tri Samnuzulsari; Jalaluddin Abdul Malek (Department of Government Studies Universitas Muhammadiyah Makassar, 2021)
Previous studies identified numerous performance predictors of employees in public sector organizations. The literature on the relationship between religiosity and public service motivation in organizations is limited. Therefore, this study aimed to address this gap and examine the link between religiosity, public service motivation, and employee performance. The data were collected from 250 public servants of the Indonesian Kepulauan Riau provincial government and analyzed using structural equation modelling (SEM). The results showed a hypothesized model that positively promotes employee performance by religiosity and public service motivation, which agrees the relationship between religiosity and performance. This study contributes to the body of knowledge concerning the contemporary literature on human resource management in the public sector by considering religiosity and public service motivation as two crucial factors enhancing employee performance. Moreover, it provides a practical guide for policymakers and managers in enhancing employee performance by adequately implementing and facilitating public service motivation and religious practices in the workplace.